Frans Krajcberg: história de vida e processo de criação - Oliveira, Uillian Trindade (2015)
Frans Krajcberg: life story and process of creation is a Doctoral Thesis that intends to bring about reflections considering the life story and the process of creation of this Polish artist naturalized Brazilian, with the intention of supporting the proposition that there might be deviations or, in Deleuze‟s and concept, lines of flight for the areas of Education and Art. In doing so, I make use of theoretical and methodological approaches to his life story and process of creation, having Deleuze (1997; 2011), Deleuze and Guattari (1992; 2010) and Haguette (2010) as main references. Having Frans Krajcberg‟s life and work as a centre, these resourses are related to Deleuze‟s concepts of rizoma, territorialization, deterritorialization, reterritorialization. Besides, I take as a basis for the analysis of the life and works of the artist the literature available about life story and processes of creation, interviews and the friendship that my family and I had with the artist. I believe that this proximity contributed significantly with this study, since it was an enabling factor of its development. Thereby, I sought to describe and analyze how the artist followed his pathway in arts until reaching issues so close and rooted to the protection of nature. Besides, I intend to approach singular, individual processes about the artist‟s life, as well as investigating nuances referring to his creative process in arts.